Effect of grinding and long-term storage on the toxicity of white snakeroot (Ageratina altissima) in goats. (June 2018) - Davis, T. Zane; Stegelmeier, Bryan L.; Lee, Stephen T.; Green, Benedict T.; Chitko-McKown, Carol G.
Abstract: White snakeroot ( Ageratina altissima ) contains the putative toxin tremetone and can produce a disease called "trembles" or "milk sickness". However the toxicity of tremetone has not been demonstrated in vivo. It has been reported that the plant is less toxic after drying and grinding. The objectives of these studies were to determine: 1) the toxic effect of grinding white snakeroot 4 months prior to dosing and, 2) the toxic effect of storing white snakeroot at ambient temperature for 5 years. Dried white snakeroot, ground 1 day, 1 month, and 4 months prior to dosing, was orally gavaged to goats at 2% of their body weight for up to 28 days or until they were minimally poisoned (minimal muscular weakness and increased serum creatine kinase (CK) activities). All four goats dosed with white snakeroot that had been ground 4 months previously and stored at room temperature were poisoned, became exercise intolerant, and had increased serum CK activities (>5600 U/ L). White snakeroot stored for 5 years was toxic as 3 of 5 dosed goats developed clinical disease within only 6 days of dosing even though approximately 80% of the tremetone in the plant had disappeared during the 5-year storage period. The results from this study demonstrate that previous grinding and extended storage did not significantly alter white snakeroot toxicity. The results also indicate that tremetone concentration is not the singular indicator of toxicity and that other white snakeroot toxins or toxic tremetone degradation products remain in dried, stored white snakeroot. Highlights: A report of the long term effects of storage on the toxicity of white snakeroot. A report of the effects of grinding on the toxicity of white snakeroot. A report indicating that unidentified toxins are likely in white snakeroot.